Concepts and Materials for Guidance and Counseling Programs in Elementary Schools - Rahmad Firmansyah; Neviyarni S; Yarmis Sukur; Pu’ad Maulana; Thessia Permata Bunda (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Elementary school is a formal educational institution for children that aims to produce optimal development in each individual according to their abilities or potential. In realizing its goals, therefore, it is necessary to have integration by all aspects contained in the world of education and one of them is counseling guidance. The method in this research is a literature study is a research that collects a number of literature in the form of books, journals or magazines related to counseling guidance in elementary schools. Teachers who handle problems for students are class teachers and do not have a specific program in counseling guidance services.